Successful removal of a large intratracheal tumor using the injection-time-controllable manual jet ventilator via translaryngeal approach -a case report- - Darhae Eum; Hyun Joo Kim; Wyun Kon Park (Korean Journal of Anesthesiology)
Background Removal of intratracheal tumors is challenging due to the difficulty in securing a patent airway before surgery. We report a case of successful removal using jet ventilation with an injection-time-controllable manual jet ventilator. Case A 3.3 cm-long intratracheal mass was located 5 cm below the vocal cords and obstructing 70%–80% of the trachea. Following induction, a rigid telescope under suspension laryngoscopy was used to guide the careful insertion of a hard and long catheter (inner diameter: 1.8 mm; outer diameter: 3 mm; length: 50 cm) beyond the tumor, enabling jet ventilation. The soft, lobulated mass was gradually excised using long forceps under endoscopic visualization. Anesthesia was maintained using total intravenous anesthesia. The operation lasted for 1 h and 45 min. Conclusions This device ensured oxygenation and ventilation during the endoscopic removal of a large intratracheal tumor. This approach highlights its utility in managing challenging airway obstructions.